Usinabilidade do aço de corte-fácil baixo carbono ao chumbo ABNT 12L14 com diferentes níveis de elementos químicos residuais (cromo, níquel e cobre) - Luiz, Nelis Evangelista (2007)
The purpose of this thesis was to study the machinability of low carbon free-machining leaded steel (ABNT/AISI 12L14) with different levels of residual (tramp) elements such as chromium, nickel and copper. Nine batches of steel were produced with controlled chemical composition, and with alterations in the mentioned residual levels so as to apply two levels factorial design. The technique of design and analysis of experiments (DOE) was used in the quantitative experiments. The characterization of the studied materials involved: chemical analysis, hardness and tensile strength tests and inclusion morphology. The machinability was evaluated taking into account the variation of the cutting conditions. Chip forms and types, chip thickness ratio, surface roughness, machining forces and cutting temperature were the parameters considered and studied. The conjugation between the variables of chemical composition (residual elements) and the variables of machining (cutting velocity, depth of cut and feed) allowed, for the quantitative test, the construction of a factorial design through which all the influences and interactions could be quantified. All the tests were carried out through the operation of cylindrical turning without cutting fluid. The cutting temperature tests were carried out with high-speed steel tools. The other tests were done with carbine tools. Samples of chip roots obtained by quick-stop technique and rake faces of coated and uncoated cemented carbide tools were analysed through the techniques of optical and scanning electron microscopy (SEM) and Energy Dispersive Spectroscopy (EDS). These techniques aimed at determining in what extent and how the machining parameters: cutting speed, feed rate, tool coating and the workpiece materials influence the morphology and the ruling conditions in the shear region, concerning the chip formation. The residual elements studied and the machining conditions showed significant influence on the machinability, considering practically all the parameters studied here.